Nonlinear static analysis of continuous multi-span suspension bridges - Choi, Dong-Ho; Gwon, Sun-Gil; Yoo, Hoon; Na, Ho-Sung (International journal of steel structures, 2013)
This paper performs the static analysis of multi-span suspension bridges using the deflection theory. Applying the deflection theory conventionally used in three-span suspension bridges to multi-span suspension bridges, the horizontal forces of the main cables due to live loads are obtained by converting the suspension system to the equivalent beam system and using the compatibility equation of cables for four spans. Iterative computations are used due to nonlinearity of the differential equations. The results, such as deflections and moments of girders and horizontal forces of the main cable, are compared with the finite element analysis for verification. The resultant values from two methods are almost the same. Finally, using the linearized deflection theory, parametric studies are performed by influence line analyses for parameters such as the side-to-center span ratio, the tower stiffness ratio and the sag to span ratio. From the parametric studies, alternatives to reduce displacements of girders in the center span and girder moments of all spans are investigated.